Diagnostic System of Wireless Acoustic Emission Signal Transfer for Monitoring the Oil-and-Gas Facilities - Skalsky, V.R.; Pochapsky, Ye.P.; Klym, B.P.; Simakovych, O.H.; Tolopko, Ya.D.; Velyky, P.P.; Dolishniy, P.M. (Science and Innovation, 2024)
The structure of diagnostic 8-channel system for wireless transfer of acoustic emission information during the monitoring of long-operation objects has been designed. The algorithmic software for hardware system and personal computer, which performs the system control and post-processing of acoustic emission information has been presented. The basic specifications of the system have been described.